Induction of mitochondrial biogenesis protects against acetaminophen hepatotoxicity. (October 2017) - Du, Kuo; Ramachandran, Anup; McGill, Mitchell R.; Mansouri, Abdellah; Asselah, Tarik; Farhood, Anwar; Woolbright, Benjamin L.; Ding, Wen-Xing; Jaeschke, Hartmut
Abstract: Mitochondrial biogenesis (MB) is an adaptive response to maintain metabolic homeostasis after mitochondrial dysfunction. Induction of MB during APAP hepatotoxicity has not been studied. To investigate this, mice were treated with toxic doses of APAP and euthanized between 0 and 96 h. At early time points, APAP caused both mitochondrial dysfunction and reduction of mitochondrial mass, indicated by reduced activity of electron transport chain (ETC) complexes I and IV and depletion of mitochondrial DNA (mtDNA), respectively. Both ETC activity and mtDNA gradually recovered after 12 h, suggesting that MB occurs at late time points after APAP overdose. Immunofluorescent staining of mitochondria with mitochondrial outer membrane protein Tom20 further demonstrated that MB occurs selectively in hepatocytes surrounding necrotic areas. MB signaling mediators including PPARγ co-activator 1-α (Pgc-1α), nuclear respiratory factor-1 (Nrf-1) and mitochondrial fission protein dynamin-related protein-1 (Drp-1) were induced. Pgc-1α was selectively increased in hepatocytes surrounding necrotic areas. In addition, the time course of MB induction coincides with increased liver regeneration. Post-treatment with the known MB inducer SRT1720 increased Pgc-1α expression and liver regeneration, resulting in protection against late liver injury after APAP overdose. Thus, induction of MB is an important feature during APAP hepatotoxicity and liver regeneration. Highlights: A delayed induction of mitochondrial biogenesis occurs after acetaminophen overdose. Mitochondrial biogenesis is prominent in hepatocytes surrounding areas of necrosis. Regions with enhanced mitochondrial biogenesis also upregulate liver regeneration. Pharmacological induction of mitochondrial biogenesis promotes liver regeneration.